Investigating the effects of E-CRM's Functions on customer's E-satisfaction and E-loyalty (Case Study: Digikala Online Store) - hashem aghazade; Iman Ahmadi; Mohammad Mehdi Dabiran (Journal of Information Technology Management)
Considering the importance of the factors affecting customer satisfaction and loyalty, this study aimed to investigate the relationship between performance and characteristic of a online stores – Digi-Kala in this particular case, as a perfect example of an electronic customer relationship system, and customer's electronic loyalty and satisfaction. As a practical-descriptive, research, electronic questionnaires were distributed among customers of Digikala , In which, functions of internet shopping system have been linked into three stages; before- purchase, during-purchase, after-purchase, and its relations with electronic loyalty and satisfaction have been estimated using structural -equations method. Based on the results, satisfaction of E-CRM's functions affected electronic loyalty and satisfaction. Also, satisfaction of during-purchase and after-purchase functions affected electronic satisfaction. However, the, effect of satisfaction in before-purchase functions in the electronic relation system has not been proven on satisfaction electronic customer's. Furthermore, the effect of satisfaction in system's functions in the whole stages has been proven on loyalty electronic.